Acute Exacerbation of COPD in the Elderly with Chronic Hypertension, Suspected Meniere's Disease and History of Active Smoking - Erwin Kurniawan; Arief Alamsyah; Dewi Mustika; Endah Listya Anggraeni (Jurnal Ilmu Kedokteran Keluarga, 2022)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a clinical symptom consisting of a group of chronic, progressive, and ongoing respiratory conditions. Meniere's Disease (MD) is a disorder of the inner ear characterized by hearing loss, tinnitus, and vertigo. Objective: Cases of COPD and MD in the elderly. Case: A 72-year-old man came to the primary clinic with the main symptoms of acute shortness of breath and vertigo. On physical examination there was an increase in the respiratory rate and wheezing in both lung fields and on the chest X-ray there was empphysematous lung. Neurological examination revealed hearing and balance problems. The patient was diagnosed with COPD and MD, with a history of active smoking for 30 years, and did not regularly visit the hospital. In this case, comprehensive interventions were carried out including Patient Centered, Family Focused, and Community Oriented. Conclusion: COPD and MD are chronic diseases that can cause acute symptoms and can recur, so that if they occur in the elderly it can reduce quality of life and mortality. Comprehensive intervention is needed to prevent the recurrence of dyspnea, vertigo, and complications. Abstrak Latar Belakang: Penyakit Paru Obstruktif Kronik (PPOK) adalah sindrom klinis yang mencakup sekelompok kondisi pernapasan kronis, progresif, dan melemahkan. Meniere Disease (MD) adalah gangguan pada telinga bagian dalam yang ditandai dengan gangguan pendengaran, tinitus, dan vertigo. Tujuan: Menampilkan kasus PPOK dan MD pada lansia. Kasus: Laki-laki berusia 72 tahun, datang ke poliklinik pratama dengan gejala utama sesak nafas akut dan vertigo. Pada pemeriksaan fisik terdapat peningkatan laju nafas dan wheezing di kedua lapang paru dan pada foto thoraks terdapat empfisematous pulmo. Pada pemeriksaan neurologis didapatkan kemungkinan gangguan pendengaran dan keseimbangan. Pasien didiagnosis secara holistik dengan PPOK dan MD, dengan riwayat perokok aktif selama 30 tahun, dan tidak rutin memeriksakan diri ke rumah sakit. Kasus ini dilakukan intervensi komprehensif meliputi Patient Centered, Family Focused, dan Community Oriented. Kesimpulan: PPOK dan MD merupakan penyakit yang kronis yang dapat menimbulkan gejala akut dan dapat kambuh, sehingga apabila terjadi pada lansia kaan dapat menurunkan kualitas hidup dan mortalitas. Diperlukan intervensi komprehensif untuk mencegah terjadinya kekambuhan sesak dan vertigo serta mencegah terjadinya komplikasi. Kata kunci: PPOK, Meniere Disease, holistik, komprehensif Dimensions Index : https://app.dimensions.ai/details/publication/pub.1154332704